1998
DOI: 10.3758/bf03201132
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing everyday memory: Signs and handedness

Abstract: Memory for frequently encountered road signs was investigated. In Experiment 1, the average level of recall of road sign features was found to be only 47%. In Experiment 2, more left-handed than righthanded people recalled that a walking figure faces right on one sign, whereas more right-handed than left-handed people recalled that a digging figure faces left on another sign. Performance thus reflected not a difference in level of mnemonic ability between left-handed and right-handed groups but instead the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
3
31
0
1
Order By: Relevance
“…Marmie and Healy (2004;see also Rinck, 1999) found that recall of the features of coins and their spatial position was much improved after just 15 sec of intentional learning and that intentional study produced large benefits, even when recall was delayed by one week. Their results suggest that reports of strikingly poor memory for common objects (e.g., Martin & Jones, 1998;Nickerson & Adams, 1979) are due to people's failure to encode information because it is not useful for the everyday use of the objects (e.g., knowing the direction that a head faces on a coin). This suggests that little detailed visual information may be stored following incidental learning of even highly familiar objects.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Marmie and Healy (2004;see also Rinck, 1999) found that recall of the features of coins and their spatial position was much improved after just 15 sec of intentional learning and that intentional study produced large benefits, even when recall was delayed by one week. Their results suggest that reports of strikingly poor memory for common objects (e.g., Martin & Jones, 1998;Nickerson & Adams, 1979) are due to people's failure to encode information because it is not useful for the everyday use of the objects (e.g., knowing the direction that a head faces on a coin). This suggests that little detailed visual information may be stored following incidental learning of even highly familiar objects.…”
Section: Discussionmentioning
confidence: 88%
“…Since it is unnecessary to store detailed information about bicycle shape in order to distinguish bicycles from other similar objects, our stored visual representations of bicycles may themselves be sketchy. People have been found to have surprisingly poor perceptual memory for everyday objects such as coins (Nickerson & Adams, 1979) and road signs (Martin & Jones, 1998). Marmie and Healy (2004;see also Rinck, 1999) found that recall of the features of coins and their spatial position was much improved after just 15 sec of intentional learning and that intentional study produced large benefits, even when recall was delayed by one week.…”
Section: Discussionmentioning
confidence: 99%
“…In an early series of experiments, we studied how one element of an object (e.g., its color) could act as a retrieval cue for another element (e.g., its location), using photographs of real objects such as cups and bottles (see, e.g., Jones, 1976Jones, , 1978. In a more recent series, we have focused on distortions of memory for the appearance of everyday objects such as road signs or cell phones (e.g., Jones & Martin, 2004;Martin & Jones, 1998, 2007. However, such studies have accepted the occurrences of certain objects in the environment as a given, and have focused on exploring their mnemonic consequences.…”
mentioning
confidence: 99%
“…Rather than divorcing cognitive information retrieval processes from perceptual information acquisition processes, as models of memory tend to do, an embodiment perspective regards cognitive processing as a re¯ection of perceptual action and argues that it may use the same computational pathways as perceptual action (see also Glenberg & McDaniel, 1992;Logan, 1995). Speci®cally, the cognitive system may take advantage of sensory-motor primitives (Kosslyn, 1994; see also Martin & Jones, 1998) which aord a computational advantage when resolving questions such as the location of an object in one's surroundings. However, in the case of the coronal and sagittal vertical environments in which we do not have additional perceptual experience at orienting, the cognitive-perceptual system may not have an existing computational method that can be accessed to facilitate orienting in those planes.…”
Section: Discussionmentioning
confidence: 98%